A DUAL-CHANNEL SUPPLY CHAIN STRUCTURE ANALYSIS OF CONSUMER BEHAVIOR IN SHOPPING CHANNEL PREFERENCES - Novawanda, Olyvia; Andi Besse Riyani Indah (Tekmapro, 2024)
Physical stores and online stores are one way that companies can continue to survive amidst competition by increasing profits from these two channels. Clothing is one of the textile commodities that is widely traded through physical stores and also online stores. This research identifies the factors that have the most significant influence on consumer preferences in choosing physical stores or online stores. Determining the factors involved adopts the results of previously conducted research. Based on existing research, there are several factors, namely Financial Risk (FR), Performance Risk (PerR), Psychological Risk (PsyR), Perceived Risk (PR), Environment Quality (EQ), Service Quality (SQ), Internet Experience (IE ), and Switching Intention (SI). From these variables, 8 hypotheses were formed. All hypotheses from the model were processed using Structural Equation Modeling with SmartPLS 3 software, it was found that H1, H2, H3, H4, H5, and H7 were accepted. H6 and H8 are rejected.